Contemporary Accounting Research: A Retrospective between 1984 and 2021 using Bibliometric Analysis* - Baker, H. Kent; Kumar, Satish; Pandey, Nitesh; Kraus, Sascha (Contemporary Accounting Research, 2023)
ABSTRACT This study critically evaluates research published by Contemporary Accounting Research ( CAR ) between 1984 and 2021 using bibliometric analysis. We examine the following: (i) CAR 's publication quality and the factors associated with its citations and (ii) CAR 's scope regarding research diversity, methods, authors geographical dispersion, and collaborative networks. The methodology permits observation of finer collaboration details and research patterns not apparent by simply categorizing the data. We use tools such as performance analysis, coauthorship analysis, bibliographic coupling, and regression analysis. The bibliometric analysis shows improvement in CAR 's CiteScore and source‐normalized impact per paper over time, consistent with publishing high‐quality research. Our analysis reveals that authors' geographical affiliations, research subject areas, and research methods are not systematically associated with citations across our various subsamples. A notable exception is that research on audit topics generates more citations than studies examining financial accounting topics. Other factors significantly and positively associated with citations include article age, article length, number of authors, order of author names, and number of references. We also show that CAR has become more diverse regarding author affiliations, subject areas, and research methods than most leading accounting journals. Only Accounting, Organizations and Society emerges as more diverse, thereby serving as a benchmark for CAR in the future. CAR should consider focusing on high‐interest areas to boost citations and tightening its acceptance criteria.